"I Have a Voice": Reexamining Researcher Positionality and Humanizing Research With African Immigrant Girls. (2nd January 2020) - Lee, Crystal Chen
Abstract : This personal perspective piece examines the researcher's positionality through the stance of humanizing research in multiethnic youth communities. Drawing on Paris and Paris and Winn's notions on humanizing research, this article reexamines positionality by revisiting two subjectivities in a three-year qualitative case study with African immigrant girls. This reexamination considers the ways in which the research and the participants participated in dialogic consciousness-raising that were personal and interconnected. Overall, this personal essay analyzes the ways in which the researcher and the participants fostered relationships while transforming their communities to reflect and act upon the world around them. In doing so, they explored the humanizing nature of what it means to "have a voice" together.